Forensic Linguistics of Hate Speech on Social Media against President Joko Widodo by Chairman of UGM’s Student Executive Board - Marista Dwi Rahmayantis; Andri Pitoyo; Sujarwoko Sujarwoko; Chelya Ilham Ramdani Putra; Achmad Fathoni Firmansyah (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This research discusses the hate speech delivered by the chairman of BEM UGM against President Joko Widodo, uploaded on social media. This research uses a forensic linguistic approach to examine the forms of hate speech by the BEM UGM chairman against President Joko Widodo. The urgency lies in understanding the impact of hate speech on social media to prevent conflicts and law violations. This research used a descriptive qualitative method with a data collection technique through the Listening-Taking Note method. Data were obtained from video transcriptions and social media posts containing the statement of the Chairman of BEM UGM. Furthermore, the data were analyzed by classifying it based on five forms of hate speech. The results show that there are five forms of hate speech delivered by the Chairman of BEM UGM against President Joko Widodo: (1) hate speech in the form of insults, such as calling the President a ‘Javanese Machiavelli’ and using derogatory words; (2) hate speech in the form of defamation, such as accusations of being a ‘ruler who destroys the democratic system’; (3) hate speech in the form of provocation, such as calls to fight the government; (4) hate speech in the form of spreading false news, such as the issue of a three-term presidency and accusations of nepotism; and (5) hate speech in the form of unpleasant actions, such as the installation of billboards calling the President ‘the most embarrassing UGM alumni’. The findings also show that these hate speeches are often not supported by factual evidence, so they are assumptions and slander. Thus, this research illustrates the importance of awareness in using social media wisely so as not to violate legal norms and communication ethics.